Integration of Technology in EFL Writing Instruction: A Systematic Review of Insights from SIELE Journal Articles - Angraini, Desti; Sulistiyo, Urip; Haryanto, Eddy; Riady, Yasir (PPSDP International Journal of Education, 2024)
This systematic review examines the integration of technology in English as a Foreign Language (EFL) writing instruction, focusing on articles published in the SIELE Journal from 2019 to 2024. Utilizing the PRISMA methodology, the study synthesizes findings on the effectiveness of digital tools in enhancing EFL writing skills. The analysis indicates that technology significantly boosts student engagement, writing proficiency, and the quality of feedback provided to learners, making the learning process more interactive and conducive to writing development. However, several challenges impede the full potential of technology integration, such as varying levels of digital literacy among students and educators, inconsistent access to technology and internet, and the need for comprehensive teacher training programs. Addressing these issues is crucial for maximizing the benefits of technology in EFL writing instruction. By overcoming these barriers, educators can better leverage digital tools to improve educational outcomes, equipping students with essential skills for success in an increasingly digital world. This research underscores the transformative role of technology in modern education.